Forestry Affairs In The Law Of The Republic Of Indonesia Number 23 Of 2014 Concerning Local Government: A Review - Agung Wicaksono (Jurnal Kajian Pemerintah: Journal of Government, Social and Politics, 2022)
This research studies forestry affairs in the Republic of Indonesia Law Number 23 of 2014 concerning Local Government. There has been a significant change in authority regarding the authority related to forestry affairs. The central government has more power than the provincial and district/city governments. The smallest authority is at the district/city government level, where only the authority is given to the management of community forest parks (TAHURA), resulting in the absence of a forestry service in the district/city government. The provincial government is an institution that has sufficient power in forestry management, although its authority is still not as large as the central government. This paper is expected to provide a complete understanding to the general public regarding the authority of each level of government.